Effect of Recombinant Human Growth Hormone Treatment in a Patient with Short Stature Associated with the Ring Chromosome 17 Syndrome - Gustavo Tempone Cardoso Penna; Gabriela de Rezende Lelot; Ana Luiza de Rezende Lelot; Juliana Greghi Hernandez; Carolina Costa Figueiredo; Nara Michelle de Araujo Evangelista; Vania de Fatima Tonetto Fernandes; Guido de Paula Colares Neto (Case Reports in Pediatrics)
Background. Ring chromosome 17 syndrome is a rare hereditary disorder whose prevalence is less than 1 : 1.000.000. We present a ten-year-old patient with ring chromosome 17 syndrome who had short stature and was treated with recombinant human growth hormone (rhGH). Case Report. A ten-year-old male scholar had moderate left conductive deafness, left kidney hypoplasia with hypertension, epilepsy, malformations in hands, feet, and abdomen, and disproportionately short stature. Despite no evidence of growth hormone deficiency, rhGH treatment was indicated as a therapeutic test due to his decelerated growth velocity and severe short stature. As a result, his growth velocity increased by 4.2 cm per year and his stature Z-score increased (from −5.87 to −5.23). Conclusion. The patient’s severe short stature may be related to genetic, environmental, and hormonal factors and the positive response to rhGH may indicate abnormalities in the somatotropic axis that were mitigated with the treatment. Although rhGH associated with adequate comorbidities controls improved his growth velocity and height Z-score, its effects in the long term are still unclear.